The Speed of Justice - Kondylis, Florence (World Bank, Washington, DC, 2018)
This paper estimates the impact of a procedural reform on the efficiency and quality of adjudication in Senegal. The reform gave judges the duty and powers to conclude pre-trial proceedings within four months. A staggered rollout and three years of high-frequency data on court cases are combined to construct an event study. Estimates suggest a reduction in pre-trial formalism: duration decreases by 46 days, the number of hearings is reduced, and judges impose more deadlines. The effects are similar for small and large cases, and across slow and fast judges. Quality does not appear to be adversely affected, while firms positively value faster adjudication.